(untitled) - Gajdzik, Peter; Sulgan, Marian (Doprava a spoje, 2010)
This paper brings information about the Toyota Production System and its fourteen manufacturing principles, exploited in automobile industry in the situation when automobile factories are looking for new ways in the world depression.